“How Are People Going to Teach This if They Don’t Know About It?”: An Interpretive Descriptive Study of Undergraduate Nurse Educators’ Experiences With Gender Inclusive and Affirming Practices - Crawford, Jess; Kramer, Marnie; Ristock, Janice; Schultz, Annette; Antonacci, Rosetta; Cervantes, Amanda; Killam, Laura; Tsui, Joyce (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2026)
Gender inclusive and affirming practices expand on gender affirming care, normalizing gender diversity and recognizing that transgender and gender diverse (TGD) people exist within institutions—beyond being recipients of care—as nurses and nursing students. Gender inclusive and affirming practices draw on Hafferty’s (1998) three levels of curriculum framework, where formal curriculum is what is taught (e.g., gender affirming care), informal curriculum is how relationships provide unscripted learning (e.g., introductions with pronouns), and hidden curriculum is how environments are experienced (e.g., gender inclusive washrooms). Using initial and follow-up interviews, this interpretive descriptive study explored undergraduate nurse educators’ (n = 7) experiences with gender inclusive and affirming practices. Analysis drew on queer theory and the three levels of curriculum framework. Findings are presented across each level of curriculum. In the formal curriculum, nurse educators are implementing gender affirming care instruction despite significant barriers. At the informal level, gender inclusive and affirming practices are being championed by a few individuals across nursing institutions, which risks perpetuating cisnormativity. At the hidden level, schools of nursing are often not gender inclusive environments, lacking inclusive washrooms and TGD faculty and staff representation. The final theme outlines recommendations from nurse educators to integrate gender inclusive and affirming practices: opportunities for ongoing learning, gender affirming care as a curriculum requirement, evaluation, and shifting nursing values. Implications from this work include the necessity to support educators learning in gender affirming care, improve gender inclusive language, improve TGD representation, and evolve structural nursing changes, such as curriculum-shaping bodies (e.g., accreditors, regulators) explicitly naming gender affirming care in crucial practice documents.